APLIKASI PENGELOLAAN MATA KULIAH TEKNIK INFORMATIKA BERBASIS CLIENT SERVER PADA STMIK PALANGKARAYA - Herkules, Herkules (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2020)
As a college education institution, STMIK Palangka Raya plays a role in the development of science, especially in the field of information technology. As a consequence of that, STMIK Palangka Raya should apply and use information technology to optimize the process of education that it organizes. So far, course information send by lecturers through word of mouth at STMIK Palangka Raya. so the authors feel there needs to use information technology to send the course information effectively by way of making the Application of Informatics Engineering Course Management in Client Server based at STMIK Palangka Raya. The purpose of this research is to help lecturers convey information such as course schedules, course assignments, course files, and course grades to students through application with internet connection. Based on the results of questionnaires made with google form service and disseminated to college students through social media with 13 respondents has filled the questionnaire, the Application of Informatics Engineering Course Management in Client Server based at STMIK Palangka Raya can be said to be worthy to use and proper to implement with the percentage of 83%.